Honokiol Eliminates Human Oral Cancer Stem-Like Cells Accompanied with Suppression of Wnt/β-Catenin Signaling and Apoptosis Induction. (10th April 2013) - Yao, Chih-Jung; Lai, Gi-Ming; Yeh, Chi-Tai; Lai, Ming-Tang; Shih, Ping-Hsiao; Chao, Wan-Ju; Whang-Peng, Jacqueline; Chuang, Shuang-En; Lai, Tung-Yuan
Abstract : Honokiol, an active compound of Magnolia officinalis, exerted many anticancer effects on various types of cancer cells. We explored its effects on the elimination of cancer stem-like side population (SP) cells in human oral squamous cell carcinoma SAS cells. The sorted SP cells possessed much higher expression of stemness genes, such as ABCG2, ABCC5, EpCAM, OCT-4, CD133, CD44, and β -catenin, and more clonogenicity as compared with the Non-SP cells. After 48 h of treatment, honokiol dose dependently reduced the proportion of SP from 2.53% to 0.09%. Apoptosis of honokiol-treated SP cells was evidenced by increased annexin V staining and cleaved caspase-3 as well as decreased Survivin and Bcl-2. Mechanistically, honokiol inhibited the CD44 and Wnt/ β -catenin signaling of SP cells. The Wnt signaling transducers such as β -catenin and TCF-4 were decreased in honokiol-treated SP cells, while the β -catenin degradation promoting kinase GSK-3 α / β was increased. Consistently, the protein levels of β -catenin downstream targets such as c-Myc and Cyclin D1 were also downregulated. Furthermore, the β -catenin-related EMT markers such as Slug and Snail were markedly suppressed by honokiol. Our findings indicate honokiol may be able to eliminate oral cancer stem cells through apoptosis induction, suppression of Wnt/ β -catenin signaling, and inhibition of EMT.